Kontribusi Politik Ekonomi Pertanian dalam Penyediaan Bahan Baku Halal di Indonesia - Cahyani, Putri Tri; Shaleh, Chaerul; Rasyid, Fauzan Ali (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
The agricultural sector is a vital component of a nation's economy as it provides food supplies and serves as a source of livelihood for millions of people. In the context of Indonesia, with its predominantly Muslim population, the significance of the agricultural sector has grown alongside the increasing demand for halal raw materials. However, the implementation of agricultural political economy policies to support the provision of halal raw materials faces several challenges, including farmers' lack of understanding of halal standards, dependence on imported raw materials, and limited infrastructure and technology. This study employs a qualitative approach using library research methods to analyze the contribution of agricultural political economy policies in supporting the provision of halal raw materials, including identifying relevant challenges and solutions. The findings reveal that policies such as agricultural land protection, fertilizer subsidies, and the development of halal industrial zones have provided a robust foundation for establishing a halal agricultural ecosystem. Nonetheless, strategic measures, such as educating farmers, enhancing local production, and investing in modern technology, remain necessary to overcome the existing obstacles. This study concludes that adaptive and inclusive agricultural political economy policies can strengthen the role of the agricultural sector in sustainably supporting the availability of halal raw materials while simultaneously enhancing the competitiveness of Indonesia's halal products in global markets.